Root sum of roots.

Level pending

a + b \sqrt{a} + \sqrt{b} is root of a monic polynomial of grade 4 with integers coefficients x 4 + a 3 x 3 + a 2 x 2 + a 1 x + a 0 x^4 +a_{3}x^3 +a_{2}x^2 + a_{1}x + a_{0} , where a a and b b are coprime integers. We know that a 2 = 10 a 0 a_{2} = -10 a_{0} and the sum of the coefficients is 2 a b -2a -b .

Find ( a 4 b ) 2 (a-4b)^2


The answer is 25.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

The minimal "integer-coefficiented" monic polynomial such that P ( a + b ) = 0 P(\sqrt{a}+\sqrt{b}) = 0 can be found by knowing that all of a + b \sqrt{a}+\sqrt{b} conjugates are also roots. It means

P ( x ) = ( x a b ) ( x a + b ) ( x + a b ) ( x + a + b ) P(x) = (x-\sqrt{a}-\sqrt{b})(x-\sqrt{a}+\sqrt{b})(x+\sqrt{a}-\sqrt{b})(x+\sqrt{a}+\sqrt{b}) P ( x ) = x 4 2 ( a + b ) x 2 + ( a b ) 2 \Rightarrow P(x) = x^4 -2(a+b)x^2 +(a-b)^2\ .

From the problem statements, we have that the first expression α \alpha shows us 2 ( a + b ) = 10 ( a b ) 2 ( a b ) 2 = a + b 5 2(a+b) = 10(a-b)^2 \Rightarrow (a-b)^2 = \frac{a+b}{5} .

Also, we get the other expression, β \beta , shows 1 + 2 ( a + b ) + ( a b ) 2 = 2 a b ( a b ) 2 b + 1 = 0 1 + -2(a+b) + (a-b)^2 = -2a-b \Rightarrow (a-b)^2 -b + 1 = 0 .

Putting α \alpha inside β \beta , we get a + b 5 b + 1 = 0 a 4 b 5 = 1 ( a 4 b ) 2 = 25. \frac{a+b}{5} -b + 1 = 0 \Rightarrow \frac{a-4b}{5} = -1 \Rightarrow \boxed{(a-4b)^2 = 25.}

Awesome exercise, Marco! Keep it up, man!

Marco Massa
Dec 27, 2013

Let c = a + b c = \sqrt{a} + \sqrt{b} , so c 2 = a + b + 2 a b c^2 = a+b + 2 \sqrt{ab} > ( c 2 ( a + b ) ) 2 = 4 a b (c^2 -(a+b))^2 = 4ab

c 4 + ( a + b ) 2 2 ( a + b ) 2 c 2 4 a b = 0 c^4 + (a+b)^2 -2(a+b)^2c^2 - 4ab = 0

and so a + b \sqrt{a} + \sqrt{b} is root of the polynomial x 4 2 ( a + b ) x 2 + ( a b ) 2 x^4 -2(a+b)x^2 +(a-b)^2

The coefficients are: a 4 = 1 ; a 3 = 0 ; a 2 = 2 ( a + b ) ; a 1 = 0 ; a 0 = ( a b ) 2 a_{4} = 1 ; a_{3} = 0 ; a_{2} = -2(a+b) ; a_{1}= 0 ; a_{0} = (a-b)^2

So we have 2 ( a + b ) = 10 ( a b ) 2 -2(a+b) = -10(a-b)^2

a + b = 5 ( a b ) 2 \boxed {a+b = 5(a-b)^2}

Now considering the sum: 2 a b = i = 0 4 a i = 1 2 ( a + b ) + ( a b ) 2 -2a -b = \sum_{i=0}^4 a_{i} = 1-2(a+b) + (a-b)^2

1 + ( a b ) 2 2 a 2 b = 2 a b 1+ (a-b)^2 -2a -2b = -2a -b

( a b ) 2 b + 1 = 0 (a-b)^2 -b +1 = 0

( a b ) 2 = b 1 (a-b)^2 = b-1

Sobstitute the last expression in the boxed expression up

( a + b ) = 5 ( b 1 ) (a+b) = 5(b-1)

a 4 b = 5 a-4b = -5

And finally ( a 4 b ) 2 = ( 5 ) 2 = 25 (a-4b)^2 = (-5)^2 = \boxed{25}

* NOTE: * a , b a ,b are in the form a = 4 n + 3 ; b = n + 2 a =4n +3 ; b = n+2 and for every value of n n are coprime.

Comments:

1 - For n = ( 1 ; 2 ; 3 ) n= (-1; -2; -3) , a a and b b are not coprime.

2 - What if we have a b = 7 5 a \wedge b = 7 \wedge 5 ? These are not attained by the parametric values you submitted, but still your problem remains true.

Guilherme Dela Corte - 7 years, 5 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...